An evaluation of project management tools and techniques in Vietnam - Quynh Le Hua Xuan; Massoud Moslehpour; Dat Tran Tien (Management Science Letters, 2019)
Project management tools and techniques provide the efficiency and effectiveness in managing and handling the projects. Many tools and techniques have been discovered and applied widely for a long period of time among project managers around the world with great contributions to the success of projects. Vietnam is a developing country and has become an attractive hub for national and international business opportunities. Consequently, there has been an increasing development and expansion of business projects in Vietnam. The purpose of this study is to analyze the use of project management tools and techniques in Vietnam. More specifically, this study aims at investigating: 1) the awareness of business people related to projects, 2) the application of project management tools and techniques within the organization and 3) the challenging obstacles that have prevented organizations in using the tools and techniques. The mixed-method methodology is employed to collect and analyze the data. This study uses interview and questionnaire techniques to collect the data for the study. Several companies in different industries in Vietnam participated in collection of the data. The findings of the study indicate lack of indepth understanding and recognition of project and project management tools and techniques in Vietnamese businesses. The term “project” has not yet become popular in Vietnam. Hence, companies in Vietnam have been facing many obstacles with the application of project management tools and techniques affected on the performance of the projects. The study suggests that the definition and recognition of Project Man-agement should go beyond the current assumption of the Vietnamese business people. Better exercises and practices of the concept of Project Management can benefit the local and international companies. Achieving higher awareness of projects and project management tools can significantly improve economic success of Vietnam.